MULTILINGUAL EDUCATION AND THE PEDAGOGICAL MODEL FOR LEARNING FOREIGHN LANGUAGES IN EARLY EDUCATION - HADÎRCĂ, Maria; STRAISTARI-LUNGU, Cristina (Acta et Commentationes, Sciences of Education, 2019)
The article highlights the educational model designed to rationalize education in the 21st century, puts the issue of multilingual education, describes a hypothetical model of foreign language learning in pre-school education and supports the need for the activity of learning a foreign language at this stage of the entire educational process, thought as a continuum.